Avoiding Major Hepatectomy with Oncological Clearance in Carcinoma Gallbladder with Right and Aberrant Hepatic Artery Involvement: A Case Series - Maharjan, Prabir; Regmee, Sujan; Ghimire, Roshan; Maharjan, Dhiresh K.; Thapa, Prabin B. (The Surgery Journal, 2025)
Gallbladder neck cancer often presents with unique surgical challenges due to its anatomical proximity to the hilum and adjacent critical vascular structures. Aberrant vascular anatomy adds to its complexity. Achieving a complete oncological clearance while preserving liver function becomes particularly difficult when the future liver remnant is inadequate. Preoperative strategies, such as biliary drainage and innovative vascular interventions like hepatic artery (HA) embolization, can play a pivotal role in optimizing surgical outcomes and minimizing the need for major liver resections. This study highlights the effectiveness of these approaches in a series of complex cases.To evaluate strategies to prevent major liver resection in gallbladder neck cancer patients with the involvement of the aberrant right HA (RHA) and inadequate future liver remnant.This retrospective case series included five patients with gallbladder neck cancer and aberrant RHA involvement who underwent surgery at the Department of GI and General Surgery, Kathmandu Medical College and Teaching Hospital, from January 1, 2020, to February 1, 2025. Preoperative biliary drainage (PTBD) and vascular interventions were employed, including embolization and reconstruction. Intraoperative findings, surgical outcomes, and postoperative recovery were analyzed.Among the five patients, one underwent embolization of a replaced RHA (rRHA), two required vascular reconstruction, and the remaining two underwent ligation of the RHA. The patient with obstructive jaundice with a rRHA developed adequate collateral supply following embolization, with simultaneous PTBD. This approach prevented major liver resection despite inadequate functional liver reserve (FLR). The study included three males and two females, with a mean age of 58 ± 5 years. Complete pathological resection (R0) was achieved in all five patients. Postoperative liver function was preserved in all cases, with one patient experiencing a posthepatectomy bile leak that resolved with conservative management. The 90-day postoperative morbidity rate was 20%, with no mortality.PTBD and selective vascular interventions, such as HA embolization and reconstruction, are effective strategies for managing gallbladder neck cancer with RHA involvement and inadequate FLR. These approaches optimize surgical outcomes, minimize the need for major liver resection, and preserve liver function in high-risk patients. Tailored preoperative planning and a multidisciplinary approach are critical in achieving favorable results in these complex cases.
Keywords: aberrant right hepatic artery; biliary drainage; gallbladder neck cancer; hepatic artery embolization; obstructive jaundice; surgical oncology; vascular reconstruction